Dinamika Manajemen Organisasi Wallet Dhuafa Jawa Timur: Studi Kasus Manajemen Program Kemanusiaan - Mafhar, Moh. Asif Roy; Imas Maesaroh; Bagoes Malik Alindra (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2025)
This study aims to describe the Dynamics of Dompet Dhuafa East Java Organizational Management: A Case Study in the Management of Humanitarian Programs. The focus of this study is how the Dynamics of Dompet Dhuafa East Java Organizational Management. This study uses a qualitative method with a descriptive analytical model. The data collection techniques used in this study are observation, interviews, and documentation. Then, the data analysis technique used in this study is the Miles and Huberman analysis technique. The results of this study explain that the dynamics of Dompet Dhuafa East Java management show the ability to adapt and be resilient in facing challenges, remaining loyal to its humanitarian mission. In addition, the dynamics of Dompet Dhuafa East Java management are influenced by various factors. External: socio-economic changes, government regulations, and socio-political conditions affect program and operational needs. Internal: integrity, transparency, organizational culture, leadership, political dynamics, and financial management determine public trust and operational efficiency. Technology: developments in information technology affect fundraising and program management. Geographic and environmental: conditions in East Java affect the accessibility of assistance. Demographic and social: characteristics and needs of the community are important for designing effective programs. Risk management includes security, finance, and reputation to face challenges and negative impacts.